Impossible differential cryptanalysis of Saturnin algorithm - Zilong JIANG; Chenhui JIN (Tongxin xuebao)
A lightweight block cipher, Saturnin, is an AES-like algorithm.In a resource-constrained environment, Saturnin can also provide high security.The impossible differential analysis on Saturnin was proposed.First, based on the structure of Saturnin, the sufficient condition of 3.5-round impossible differential distinguisher of Saturnin was presented and proved, and 270.1truncated impossible differential distinguishers could be quickly constructed by utilizing the sufficient condition.Then, from the constructed 270.1distinguishers, the 64 distinguishers could be picked out pointedly and classified into four types.Four attack trails could be obtained by appending two rounds before the four types of distinguishers.These four attack trails had the same plaintext structure and a number of common subkey bits.With the help of these two properties, the complexity of the attack scheme could be reduced.Combined with the analysis technologies such as early abort, present the 5.5-round impossible differential attack scheme with 2176.88chosen plaintexts, 2143.88 256-bit blocks, and 2176.915.5-round encryption.As so far, this is the known attack scheme for Saturnin against impossible differential attack.